2014
DOI: 10.1128/aac.01836-13
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of GSK1322322 into Epithelial Lining Fluid and Alveolar Macrophages as Determined by Bronchoalveolar Lavage

Abstract: GSK1322322 is a potent peptide deformylase inhibitor with in vitro and in vivo activity against multidrug-resistant skin and respiratory pathogens. This report provides plasma and intrapulmonary pharmacokinetics, safety, and tolerability of GSK1322322 after repeat (twice daily intravenous dosing for 4 days) dosing at 1,500 mg. Plasma samples were collected over the last 12-hour dosing interval of repeat dosing following the day 4 morning dose (the last dose). Bronchoalveolar lavage samples were collected once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Each IV dose was administered to Cohort C at a concentration of 3 mg/mL and a rate of 500 mL/h for 60 minutes. Bronchoalveolar lavage samples were taken from volunteers in Cohort C on day 6 to analyze GSK1322322 concentration in the lung epithelial lining fluid and alveolar macrophages (manuscript in preparation) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each IV dose was administered to Cohort C at a concentration of 3 mg/mL and a rate of 500 mL/h for 60 minutes. Bronchoalveolar lavage samples were taken from volunteers in Cohort C on day 6 to analyze GSK1322322 concentration in the lung epithelial lining fluid and alveolar macrophages (manuscript in preparation) …”
Section: Methodsmentioning
confidence: 99%
“…Bronchoalveolar lavage samples were taken from volunteers in Cohort C on day 6 to analyze GSK1322322 concentration in the lung epithelial lining fluid and alveolar macrophages (manuscript in preparation). 13 Cohorts D, E, F1, and F2 received IV administration of placebo or a mesylate salt formulation of GSK1322322. Cohort D received a single IV dose of placebo or GSK1322322 2,000 mg on day 1 administered at a concentration of 5 mg/mL and a rate of 400 mL/h for 60 minutes.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Although early PDF inhibitors were recognized particularly for their microbiological activity against staphylococci, especially MRSA (203), GSK1322322 also may have useful activity against S. pneumoniae and H. influenzae, with MICs of Յ4 g/ml against these organisms in addition to drug-resistant staphylococci (204,205). Clinical studies in healthy subjects showed good penetration of the inhibitor into epithelial lining fluid and alveolar macrophages (206). Thus, the in vitro microbiological profile and bioavailability in the lung support clinical studies of this drug in respiratory disease.…”
Section: Pdf Inhibitorsmentioning
confidence: 99%
“…Moreover, plasma and intrapulmonary pharmacokinetic studies with GSK1322322 dosed intravenously twice daily for 4 days showed that its time courses in epithelial lining fluid (ELF) and alveolar macrophages (AM) mirror the plasma concentrationtime profiles. In fact, the area under the concentration-time curve from time 0 to (AUC 0 -) ratios of ELF and AM to total plasma were 1.2 and 2.5, respectively (12). Therefore, GSK1322322 should be active against intracellular L. pneumophila at the con- centrations necessary to achieve efficacy versus the other bacterial respiratory tract pathogens and may be an effective treatment for lower respiratory tract infections caused by this atypical pathogen.…”
mentioning
confidence: 99%
“…West, T. S. Collingwood, K. Aubart, D. J. Holmes, and M. Zalacain, submitted for publication). Therefore, the antibacterial activity shown by GSK1322322 against intracellular L. pneumophila may be due, at least in part, to its potent inhibition of PdfC (G. Van Aller, unpublished results), although its accumulation inside macrophages may also contribute to it (12).…”
mentioning
confidence: 99%